CONSOLIDATION IN JOINT STOCK COMPANIES PROBLEMS AND SOLUTIONS OF CASH FLOW REPORTING - Eshankulov Azamat Abdirakhimovich (Web of Journals Publishing, 2024)
Consolidation in joint stock companies involves combining financial statements of parent and subsidiary companies to present a unified financial position. This process can complicate cash flow reporting, posing several challenges. These challenges include intercompany transactions, timing differences, and the complexities of adjusting for acquisitions or divestitures. This paper explores these problems in depth and proposes solutions to improve the accuracy and transparency of consolidated cash flow reports. Key recommendations include standardizing reporting practices, enhancing intercompany transaction tracking, and implementing robust internal controls to ensure accurate and timely consolidation processes. By addressing these issues, companies can provide clearer financial insights to stakeholders and support better decision-making. If you need any modifications or additional sections, feel free to let me know!
Keywords: Consolidation, joint stock companies, cash flow reporting, financial statements, reporting practices.